2016
DOI: 10.1016/j.jval.2016.09.108
|View full text |Cite
|
Sign up to set email alerts
|

A General Model for The Estimation of Societal Costs of Lost Production and Informal Care In Italy

Abstract: We developed a general model for estimating and comparing disease-and treatment-specific lost paid/unpaid production (due to premature death and reduced ability) and informal care received (due to reduced ability) in Italy, starting from survival, demographic and Health-Related Quality of Life (HRQoL) data. Assuming the disease is not selecting a systematically different population in terms of mean wage than the general public, age-and gender-specific yearly production values are estimated combining data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the present analysis, we considered only productivity losses of employed people, excluding indirect costs of people out of the labour market. Productivity costs were estimated for different age groups to account for differences in wages, considering age and gender-specific yearly paid production value [56] and employment rates [48]. People aged 65-74 were assumed to be retired, therefore their employment rate was set equal to 0.…”
Section: Cost Analysis: Assessment Of Conditions' Costs and Estimatio...mentioning
confidence: 99%
“…In the present analysis, we considered only productivity losses of employed people, excluding indirect costs of people out of the labour market. Productivity costs were estimated for different age groups to account for differences in wages, considering age and gender-specific yearly paid production value [56] and employment rates [48]. People aged 65-74 were assumed to be retired, therefore their employment rate was set equal to 0.…”
Section: Cost Analysis: Assessment Of Conditions' Costs and Estimatio...mentioning
confidence: 99%
“…According to a recent paper concerning social costs in Italy, 20 it was decided to attribute an economic value to grandparents’ time spent caring for their grandchildren when not at school. The annual cost estimated for over-65s is €6.531 for males and €14.491 for females; these two values were balanced for the over-65s gender distribution in Italy (43% male, 57% female) and converted into a corresponding cost per day.…”
Section: Methodsmentioning
confidence: 99%
“…The Italian unit cost for proxy good method was derived from a single Italian study. 22 Several studies reported German unit costs, [23][24][25][26][27] from which the average value was calculated. Table 1 provides the hourly unit cost used in the analyses.…”
Section: Informal Care Costsmentioning
confidence: 99%